Удосконалення технології варених ковбас з рослинними добавками - Корець, Лідія Іванівна (My University, 2021)
Дисертацію присвячено науковому обґрунтуванню та розробці технології варених ковбас з рослинними добавками. За результатами комплексних досліджень отримано нові дані щодо можливості регулювання комплексу показників якості варених ковбас з рослинною добавкою пшеничної клітковини з пектином гарбуза; визначено технологічні режими попередньої підготовки рослинної добавки, а саме подрібнення до розміру 500…600 мкм, гідратація за гідромодуля 1:3 та способи її введення до складу варених ковбас. Науково обґрунтовано та експериментально підтверджено можливість збагачення варених ковбас біологічно-активними речовинами рослинної добавки пшеничної клітковини з пектином гарбуза з метою підвищення їх харчової та біологічної цінності, та відповідно до сучасних вимог нутриціології та адекватних потреб людини. Вперше науково доведено ефективність використання біологічно-активної добавки пшеничної клітковини з пектином гарбуза як технологічного чинника впливу на функціонально-технологічні та структурно-механічні властивості модельних м’ясних фаршевих систем варених ковбасних виробів. Встановлено закономірність зміни стабільності функціонально-технологічних властивостей модельних м’ясних фаршевих систем залежно від кількості внесеної добавки пшеничної клітковини з пектином гарбуза та способу її введення. Вперше встановлено позитивний вплив рослинної добавки пшеничної клітковини з пектином гарбуза на амінокислотний склад, біологічну цінність, показник перетравлюваності білків варених ковбас травними ферментами в системі «in vitro». На підґрунті комплексного дослідження варених ковбас з рослинною добавкою доведено її позитивний вплив на харчову і біологічну цінність, органолептичні показники, структуру та технологічні властивості готової продукції. Підтвердженням високої біологічної цінності ковбасних виробів є проведені дослідження в умовах «in vitro». Досліджено мікробіологічні та фізико-хімічні показники вареної ковбаси з рослинною добавкою при зберіганні, встановлено термін придатності до споживання при зберіганні за температури 0…6 °С у поліамідній оболонці, який становить 10 діб. Розроблено нормативну документацію на виробництво варених ковбас підвищеної харчової цінності із урахуванням принципів забезпечення адекватних потреб людини у незамінних факторах харчування методом комбінування сировини тваринного та рослинного походження. Проведено промислову апробацію, яка підтвердила доцільність виробництва вареної ковбаси з рослинною добавкою пшеничної клітковини з пектином гарбуза. Based on the results of complex studies, new data were obtained on the possibility of regulating the complex of quality indicators of cooked sausages with a vegetable supplement of wheat fiber with pumpkin pectin; the technological modes of preliminary preparation of the vegetable additive have been determined, namely grinding to a size of 500...600 microns, hydration according to the hydromodule 1: 3 and methods of its introduction into the composition of cooked sausages. The nutritional value of the herbal supplement has been established: protein content - 11.9%, carbohydrates - 75.8%, fat - 2.2%. The biological value of the plant supplement of wheat fiber with pumpkin pectin was determined - 89.9%, amino acids 13.48%, utilitarian coefficient - 0.68%; the content of polyunsaturated fatty acids - 28.22%; minerals (mg / 100 g): potassium - 1182, selenium - 77.6, calcium - 73.0, magnesium - 11.5, manganese - 11.5, phosphorus - 13. The herbal supplement contains vitamins A, C, beta-carotene, K, E and group B. For the first time, the effectiveness of using a dietary supplement of wheat fiber with pumpkin pectin as a technological factor of influence on the functional, technological and structural and mechanical properties of model minced meat systems of sausages has been scientifically proven. The regularity of the change in the stability of the functional and technological properties of model minced meat systems has been established depending on the amount of added wheat fiber with pumpkin pectin and the method of its introduction. The effect of a plant supplement of wheat fiber with pumpkin pectin on the physicochemical, functional, technological and structural-mechanical indicators of model minced meat of cooked sausages and organoleptic indicators of finished products has been studied. The studies conducted allow us to assert that the introduction of a plant additive in the amount of 5.0% as a functional ingredient in model minced meat of cooked sausages increases their water-holding capacity - by 5.14 ... 14.7% and fat-holding capacity - by 5.8 ... 5,9%, which will improve the structure of model samples of cooked sausages. The research results indicate an increase in the stability of minced meat systems of prototypes of cooked sausages by 5.8 ...10.5% in comparison with the control sample. It has been proven that the introduction of the plant additive wheat fiber with pumpkin pectin in the amount of 5% into the composition of cooked sausages formulations makes it possible to reduce weight loss during heat treatment by 2.08 ... 4.10%, respectively. This can be explained by the fact that the dietary fibers of the vegetable supplement have a low gelatinization temperature, close to the denaturation temperature of meat proteins, at which moisture separation occurs, ensures its absorption by the protein-carbohydrate complex introduced with the vegetable supplement. The possibility of enriching cooked sausages with biologically active substances of a plant supplement of wheat fiber with pumpkin pectin in order to increase their nutritional and biological value, and in accordance with modern nutritional requirements and adequate human needs has been scientifically substantiated and experimentally confirmed. For the first time, the positive effect of a plant supplement of wheat fiber with pumpkin pectin on the amino acid composition and biological value of cooked sausages was established. The calculation of indicators of utility and comparative redundancy testifies to a better balance of essential amino acids in the composition of prototypes of cooked sausages in comparison with the control and more rational use of them by the body and, in accordance with the established requirements of the indicators of utility, it approaches 1, the excess indicator is up to 0. The high biological value of the developed sausages is confirmed by the conducted studies in vitro. It was found that, according to the intensity of protein digestion by proteases of the gastrointestinal tract under the action of enzymes, the digestion of cooked sausages samples with a plant supplement of wheat fiber with pumpkin pectin is more accelerated. This is due to the fact that the proteins of the plant supplement of wheat fiber with pumpkin pectin are easily soluble in water and solutions of neutral salts, contributing to their faster digestion by the human body. The microbiological and physicochemical characteristics of cooked sausages with a herbal additive during storage have been investigated, the shelf life for storage at a temperature of 0 ... 6 ° C in a polyamide casing has been established, is 10 days. A comparative assessment of the quality indicators of cooked sausages proves the positive influence of the proposed additive and technological methods on the formation of consumer properties of cooked sausages. This is due to the content in the herbal supplement of highly functional plant components: vegetable protein, wheat fiber and pumpkin pectin substances, as well as functional changes in meat raw materials according to the developed technological modes. Regulatory documentation has been developed for the production of cooked sausages of increased nutritional value, taking into account the principles of ensuring adequate human needs for irreplaceable nutritional factors by combining raw materials of animal and vegetable origin. Industrial testing was carried out, which confirmed the feasibility of producing boiled sausages of increased nutritional and biological value with a vegetable supplement of wheat fiber with pumpkin pectin.
Keywords: пшенична клітковина; пектин гарбуза; функціональний продукт; біологічна цінність; варена ковбаса; wheat fiber; pumpkin pectin; functional product; boiled sausage; мікробіологія (м'ясопереробна промисловість)